Can use of probiotics drugs cause fungemia? – a literature review - Carneiro, Stefane dos Santos (2022)
Commercially, there are many products sold as probiotics composed by Sacharomyces boulardii, with probiotic drugs being those that are widely used in different clinical situations. The probiotic efficacy of these agents is proven in many studies, as well as their safety in normal use situations. However, there have been some reports of fungemias related to the use of these probiotics in hospitals associated with some factors. Therefore, our objective is to review the knowledge about this association, focusing on the factors that provide it and the development mechanisms. For the development of fungemia associated with the use of probiotics, it is observed that it has greater development potential in patients using a central venous catheter. Although this is the main factor, others that reduce the patient's immune status, as well as reduce the intestinal defense barriers, contribute to this process, increasing the risk of fungemia. Despite the well-documented benefits of probiotics, their use must be carefully evaluated for each patient, due to factors that contribute to associate the use of probiotic drugs with the risk of developing bloodstream infection by S. boulardii. It is necessary, therefore, to include protocols that generate alerts about this risk and establish preventive measures.